ACT Care: A Mobile Acceptance and Commitment Therapy Intervention to Improve Quality of Life in Breast Cancer Patients - Trishinta, Sirli Mardianna; Wahidyanti Rahayu Hastutiningtyas; Cantika Previana (Journal of Nursing Science Update (JNSU), 2025)
Breast cancer patients often experience psychological distress, such as anxiety, stress and decreased quality of life, due to treatment processes and physical changes. Addressing these challenges requires holistic nursing care that integrates physical, emotional, and psychosocial aspects. In line with the Astra Cita mission to improve community well-being through science and technology, this study developed the ACT Care Application, based on Acceptance and Commitment Therapy (ACT), to support breast cancer patients in managing psychological distress through mindfulness and self-acceptance. The application provides self-assessment, structured mindfulness exercises, reflective journaling, self-acceptance modules, and virtual community support. This study employed a Research and Development (R&D) design, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). A purposive sample of 30 breast cancer patients in Indonesia participated. Data were collected using a pretest–posttest design with the WHOQOL-BREF questionnaire. Patients used the ACT Care application for four weeks, and effectiveness was analyzed using the Wilcoxon signed-rank test. The results showed a significant improvement in the quality of life of breast cancer patients after using the ACT Care application. The mean WHOQOL-BREF score increased from 58.4 to 72.9 (P < 0.001), indicating improvements across physical, psychological, social, and environmental domains. This study provides preliminary support for the efficacy of technology-based nursing intervention to improve psychological well-being among breast cancer women. Considering these limitations, there is a need for further research to explore the benefit of ACT Care within specific cultural settings and cultures to ensure that this approach has larger applicability and acceptability.